When trade law meets public health evidence: the World Trade Organization and clove cigarettes. Issue 6 (21st July 2012) - Jarman, Holly; Schmidt, Judith; Rubin, Daniel B
Abstract : A recent trade dispute between the USA and Indonesia, overseen by the World Trade Organization, challenges piecemeal approaches to tobacco regulation.